Embodiment Practice: Using Poi Spinning in the Healing Process. Issue 2 (3rd April 2021) - Sirs, Lori Anne; Meek, Julie Marie
ABSTRACT: The authors examine the therapeutic practice of poi spinning. The Māori word "poi" refers to any singular or plural set of tethered weights that may be held in the hands and spun around the body. Drawing upon their clinical experience, they posit that poi spinning offers a unique modality to help clients with self-regulation, expression, and body awareness. They share practice wisdom and application of this modality, using case examples. Unique features of this practice include rhythmic movement, embodied flow states, creativity and emotional expression, mindful subjective experience, playfulness and positive emotion, immediate sensory feedback, reciprocal social attunement, and metaphorical learning. IMPLICATIONS: Poi spinning, as a movement modality, offers unique benefits in the therapy setting for clients who present with a variety of clinical needs and treatment goals. Poi spinning is an effective means of self-care for social workers. Poi spinning in the therapeutic milieu is a relatively new application of this practice and as such, additional research into the benefits of poi spinning as a healing practice is warranted.